Football facing a future with global warming: perspectives for players health and performance - Nybo, L.; Flouris, A. D.; Racinais, S.; Mohr, M. (British Journal of Sports Medicine, 2021)
Escalating environmental temperatures are expected to influence performance and planning of several future football events, for example, FIFA World Cups, regular league and continental cup matches and climate projections for Tokyo (Olympic Games postponed to August 2021) implies that athletes are facing high heat exposure in the next Olympic football tournament. Prompted by global warming, but also with current conditions and historic heat-events in mind, it is relevant to consider the consequences for football play and players health. Heat stress has detrimental effects on endurance performances and sudden or extreme exposure is a major health concern. Moreover, heat stress could, in some situations, create an unsportsmanlike competitive advantage for the home team and fair play may require special planning and precaution procedures.